Perkembangan Pemikiran Hukum Keluarga tentang Persamaan Hak Menerima Waris dalam Masalah Kalalah dan Radd - Muhammad Sopiyan; Siah Khosyi’ah (Prodi Hukum Ekonomi Syariah (Muamalah), 2022)
In the Qur'an, Islamic inheritance law is explained in detail, concretely and realistically, even according to mutaqaddimiin scholars these verses are qoth'iyah (definitely) which closes the space for ijtihad. Meanwhile, the current reality is different from the situation when the inheritance verse was revealed and it is possible if inheritance law is translated within the scope of Islamic society according to the conditions and social situations that surround it. This study discusses equality of rights in inheritance with a focus on issues of loss and radd, because loss requires a more comprehensive understanding. The methodology uses a descriptive analysis approach to library data by collecting library data, reading and reviewing it and then doing an analysis to constructively criticize related to kalalah and rad. The results of the study were then analyzed that the development of the concept of kalalah and rad underwent many changes but what needs to be underlined is that everything depends on the illat according to the rules of ushul fiqh al-hukm yaduru ma'a 'iltrain.